Daya anti bakteri ekstrak daun sisik naga dibandingkan dengan ekstrak daun saga, daun sirih dan kayu manis terhadap isolat bakteri dari penderita periodontitis kronis (Antibacterial effect of drymoglossum piloselloides, abrus precatoris, piper bettle and cinnamon aldehyde on isolated bacteria from periodontitis chronic patients) - Hendriani, Yenni; Sukmasari, Susi; Mulyanti, Sri (Politeknik Kesehatan Bandung, 2009)
Drymoglossum piloselloides, Abrus precatoris, Piper bettle and Cinnamon aldehyde have been traditionally used in dentistry. However, there are not many scientific research on investigating those leafs and their therapeutic efficacy to bacteria causing periodontitis. Aims: to investigate antibacterial of extracted of Drymoglossum piloselloides, Abrus precatoris, Piper bettle and Cinnamon aldehyde on black pigmented bacteria isolated from periodontitis patient. Materials and Methode: The study sample was a black pigmented bacterial taken from the fluid of gingival socket of patient with chronic marginal periodontitis. The bacteria was planted in the LAD and was isolated in the schalder medium. The examination of antibacterial effect was done using disc diffusion methods, determination of minimal concentration of bacteriostatic effect and also bactericidal effect using tube dilution methods. ANOVA test was done to analysis the differences of extracts' efficacy. Result: Antibacterial effect test using disc diffusion methods on concentration of extracts were 5%, 10 %, 15% and 20% were shown bacterial development. However there is no statistically differences on antibacterial effect among those four extracted on the disc diffusion test. The minimal bacterostatic effect of Drymoglossum piloselloides, Abrus precatoris, Piper bettle and Cinnamon aldehyde were 25o/o, 50%, 3,25% and 208 % respectively. Meanwhile, the minimal bacterial effect of Drymoglossum piloselloides, Abrus precatoris, Piper bettle and Cinnamon aldehyde were 50 %, 25%, 3,25% 41,7% respectively. Conclusion: There were differences on antibacterial effect between Drymoglossum pilloselloides, Abrus precatoris , Piper bettle and Cinnamon aldehyde particularly for black pigmented bacteria. Piper Bettle has been proven has strongest potential antibacterial.